Indacaterol/glycopyrronium versus tiotropium or glycopyrronium in long-acting bronchodilator-naïve COPD patients: a pooled analysis - Muro,S; Yoshisue,H; Kostikas,K; Olsson,P; Gupta,P; Wedzicha,JA (Respirology, 2020)
BACKGROUND AND OBJECTIVE: Indacaterol/glycopyrronium (IND/GLY) 110/50 μg once daily (q.d.) has demonstrated greater improvements in lung function, patient-reported outcomes and lower exacerbation rates versus mono long-acting muscarinic antagonists (LAMA) in chronic obstructive pulmonary disease (COPD) patients. However, data are limited on initial treatment with IND/GLY 110/50 μg q.d. versus mono LAMA in COPD patients, not previously on maintenance treatment with long-acting bronchodilators (LABD). METHODS: A pooled analysis of ARISE, SHINE and SPARK trials was conducted to evaluate the efficacy of IND/GLY 110/50 μg q.d. versus open-label (OL) tiotropium (TIO) 18 μg q.d. and GLY 50 μg q.d. in COPD patients, not on maintenance treatment with LABD at study entry (LABD-naïve). Efficacy was assessed after 24/26 weeks of treatment. RESULTS: In total, 998 LABD-naïve patients were included (IND/GLY: 353; OL TIO: 328; GLY: 317). Patients treated with IND/GLY 110/50 μg q.d. experienced greater improvements in trough forced expiratory volume in 1 s (FEV1 ) versus OL TIO 18 μg q.d. (least squares mean treatment difference (Δ): 0.086 L) and GLY 50 μg q.d. (Δ: 0.080 L) after 24/26 weeks. Improvements in electronic diary (eDiary) symptom scores, transition dyspnoea index (TDI) focal score, St George's Respiratory Questionnaire (SGRQ) total score and rescue medication use were also greater with IND/GLY versus OL TIO and GLY. Greater proportion of patients achieved minimal clinically important difference in trough FEV1 , TDI and SGRQ with IND/GLY versus OL TIO and GLY. CONCLUSION: LABD-naïve patients treated with IND/GLY 110/50 μg q.d. achieved improvements in lung function, daily symptoms, dyspnoea, health-related quality of life and rescue medication use versus those who received single LAMA.